Detection of microplastics in human colectomy specimens. Issue 1 (21st November 2020) - Ibrahim, Yusof Shuaib; Tuan Anuar, Sabiqah; Azmi, Alyza A; Wan Mohd Khalik, Wan Mohd Afiq; Lehata, Shumpei; Hamzah, Siti Rabaah; Ismail, Dzulkiflee; Ma, Zheng Feei; Dzulkarnaen, Andee; Zakaria, Zaidi; Mustaffa, Nazri; Tuan Sharif, Sharifah Emilia; et al.
Abstract: Background and Aim: While dietary exposure to microplastics is increasingly recognized, it is unknown if ingested plastics remain within the digestive tract. We aimed to examine human colectomy specimens for microplastics and to report the characteristics as well as polymer composition of the particles. Methods: Colectomy samples were obtained from 11 adults (mean age 45.7, six males) who were residents of Northeastern Peninsular Malaysia. Microplastics were identified following chemical digestion of specimens and subsequent filtration. The samples were then examined for characteristics (abundance, length, shape, and color) and composition of three common polymer types using stereo‐ and Fourier Transform InfraRed (FTIR) microscopes. Results: Microplastics were detected in all 11 specimens with an average of 331 particles/individual specimen or 28.1 ± 15.4 particles/g tissue. Filaments or fibers accounted for 96.1% of particles, and 73.1% of all filaments were transparent. Out of 40 random filaments from 10 specimens (one had indeterminate spectra patterns), 90% were polycarbonate, 50% were polyamide, and 40% were polypropylene. Conclusion: Our study suggests that microplastics are ubiquitously present in the human colon. Abstract : Eleven human colectomy samples (mean age 45.7 years old, six males) were obtained due to clinical indications (nine colon cancer and two normal histology). All 11 specimens contained microplastics (average 331 particles per individual specimen or 28.1 ± 15.4 particles per g of tissue). Microplastics are ubiquitously present in the human colon.